Overexpression of Pyrus sinkiangensis HAT5 enhances drought and salt tolerance, and low-temperature sensitivity in transgenic tomato - Liu, Xiaoyan; Li, Aowei; Wang, Saisai; Lan, Chengfang; Wang, Yize; Li, Jin; Zhu, Jianbo (Frontiers in Plant Science, 2022)
The homology domain leucine zipper protein HAT5 belongs to the HD-Zip I family and plays an important role in regulating plant growth, development, and stress resistance. In this study, we cloned the PsiHAT5 transcription factor from Pyrussinkiangensis Yü, which encodes a protein with the highest homology to Pyrus x Bretschneider. We constructed a PsiHAT5 plant overexpression vector using molecular biology and then obtained tomatoes transgenic to the PsiHAT5 gene with the help of the Agrobacterium-mediated method. The accumulation of soluble sugars, soluble proteins, and proline contents and higher superoxide dismutase (SOD), catalase (CAT), and peroxidase (POD) activities of the transgenic lines were found to be significantly higher under drought stress and NaCl stress by phenotypic and stress tolerance physiological tests. Under low temperature (cold and freezing) stress, the malondialdehyde content (MDA) and relative conductivity content of transgenic tomatoes were significantly higher than those of wild-type, and the accumulation of soluble sugars and other substances and antioxidant enzyme activities were significantly lower than those of wild-type. Thus, this study shows that PsiHAT5 confers tolerance to drought and salt stress in tomatoes by increasing the accumulation of osmoregulatory substances such as soluble sugars, soluble proteins, and proline and by increasing the activity of antioxidant enzyme systems. In conclusion, our study elucidates that the PsiHAT5 transcription factor has great potential in crop resistance breeding and lays the theoretical foundation for future research on HD-Zip family genes in field trials.